How Toxic is Milkweed when Harvested and Cooked according to Myaamia Tradition? - Everest, Michael A.; Gonella, Michael P.; Bowler, Holly G.; Waschak, Joshua R. (Ethnobiology Letters, 2019)
Asclepias syriaca L. (common milkweed) is known to contain sufficient amounts of cardiac glycosides, which are known to be toxic to humans. Nonetheless, it is traditionally used for food by Native Americans, including the Myaamia people of Indiana and Oklahoma. In order to test the hypothesis that traditional horticultural and culinary practices prevent the Myaamia from ingesting toxic levels of cardiac glycosides, we have determined the level of glycosides (digitoxin equivalent) in A. syriaca 1) in various parts of the plant, 2) at various heights for pre-reproductive plants, and 3) before and after cooking according to traditional Myaamia procedures. Plants were grown, harvested, dried, ground, and extracted twice with ethanol. The amount of digitoxin-equivalent glycoside in plant extract was determined spectrophotometrically using 2,2’,4,4’-tetranitrodiphenyl, a selective derivatizing agent. We find that all parts of the plant contain significant levels of cardiac glycosides at all stages of growth. Plants harvested as young shoots for food, the common practice of the Myaamia, contain slightly lower levels of cardiac glycosides when compared to the leaves and stems of older, taller plants. Moreover, the toxicity is significantly reduced by the traditional Myaamia cooking procedure—a repeated boiling with several changes of water. Therefore, it appears as though the risk of glycoside poisoning from traditional Myaamia use of milkweed for food is moderated by their harvesting practice and traditional cooking procedure.